Recent Advances In Halal Food Authentication: Challenges And Strategies - Ng, Pei Chi; Ahmad Ruslan, Nur Amy Syahira; Chin, Ling Xuan; Ahmad, Musa; Abu Hanifah, Sharina; Abdullah, Zanariah; Khor, Sook Mei; Pei Chi Ng; Nur Amy Syahira Ahmad Ruslan; Ling Xuan Chin; Musa Ahmad; Sharina Abu Hanifah; et al. (Institute of Food Technologists., 2024)
Indexed by WOS/SCOPUS/ERA